Models of Consumer Behaviour in Mall Culture - Panandikar, S. C.; Gupte, Rajiv (Indian Journal of Marketing, 2007)
Malls are called gigantic concrete amusement parks for the middle class in metros. In 2001, there were just three shopping malls in India. By 2007, that figure is expected to grow to 343. According to KSA Technopak’s white paper prepared with ICICI Property services, it is estimated that about 18 million square feet of mall space will be developed by 2006, in 12 major cities. As the estimate goes there are about 40,000 and 85,000 footfalls on an average in the malls like INORBIT, in Mumbai and FORUM, in Bangalore respectively. It is also expected that the retail sales of consumer goods will rise from Rs. 15,02,900 Crores in 2004 to Rs. 27,20,400 Crores by 2007, (i.e. an average annual growth of about 17%). The data available estimates that the Indian Consumer spent about 41% of their disposable income on groceries, in 2003 (India Today, Nov. 21, 2005, 2).The malls have revolutionized the concept of retailing and they pose a serious competition to their conventional counterparts in terms of service, ambience, price, access to the brands etc. Furthermore they have created a niche in the minds of consumers through a perception of innovation, style and status.